Factors affecting the determination of target costing in the mini manufacturing companies in Sudan: Field Study - Abdalla, Ezzat Kamal (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aims to achieve a number of the goals which relate to scheduling on the target costing including its definition and the stage of the deterring target costing and explaining the effects of the number of factors in the determining in manufactures companies in Sudan. This study has adopted the analytical descriptive approach. The study has concluded that target costing is one of the modern cost systems which have an approach as results of the firm competition. it depends on staring by recognizing customer needs and trying to achieve them as valuable as possible the study has also pointed out that these factors differ in the degree of effect in the process of determining target costing in Sudan based on these results the researcher has come with a number of recommendation the most important of which is that there must be a great costing deep of explanation for the theoretical framework of target costing among the companies in order to help these companies come along with the level and international competition locally and systematically. the researcher has also recommended the should be training and learning in the companies in the market competition so that manger can recognize the modernity of accounting mutuality In addition, the researcher emphasizes the importance of cost –accounting awareness of the features accomplished by application of target costing and conducting more applied and theoretical studies and taking care of the raw material price and the quality of the material.